Investigation of Alkyl–Aryl Interactions Using the Azobenzene Switch – The Influence of the Electronic Nature of Aromatic London Dispersion Donors - Schatz, Dominic; Kunz, Anne; Raab, Aileen R.; Wegner, Hermann A. (Synlett, 2022)
Herein we report the synthesis of nonsymmetrically substituted azobenzene derivatives with meta-alkyl substituents on one side and meta-aryl moieties with electron-donating or electron-withdrawing groups on the other side. The half-lives for the thermal (Z)- to (E)-isomerization of these molecules were measured in n-octane, which allows investigation of the strength of the aryl–alkyl interactions between their substituents. It was found that the London dispersion donor strength of the alkyl substrate is the decisive factor in the observed stabilization, whereas the electronic structure of the aryl fragment does not influence the isomerization in a significant way.
Keywords: London dispersion; azobenzenes; kinetics; molecular switches; CH–π interactions